Fingerprint authentication using LT codes - Pahariya P.; Singh S.K. (My University, 2025)
Biometric is used for identifying the person based on their traits. Fingerprint is one of the most important and most used biometric trait for person authentication. Fingerprint database must be stored in efficient way and in most secure way so that it is unable to hack by the hacker and it will be able to recognize the person fast in large database. In this paper, we proposed an efficient way of storing the fingerprint data for fast recognition. We are using LT codes for storing the x coordinates of minutiae points and fingerprint images is stored in encrypted form with the coordinates. We are using on-the-fly gaussian algorithm for decoding the x coordinates and calculate the value for finding similarity in between two fingerprints. c 2018 ACM. ISBN 978-1-4503-6394-5/18/05. . . $15.00